Modeling of the case depth and surface hardness of steel during ion nitriding - Mohanad, Muzahem Khalaf; Kostyk, Viktoriia; Domin, Dmytro; Kostyk, Kateryna (Eastern-European Journal of Enterprise Technologies, 2016)
Modeling of the ion nitriding process allows solving many problems of operations management, forecasting of results and development of new treatment regimes, which is an urgent issue today. The goal of the paper was modeling of the case depth and surface hardness of 38Cr2MoAl А steel during ion nitriding. The experimental data showed that the case depth varies from 20 to 620 µm in the ion nitriding temperature range of 500-560 °С and duration of 1-12 hours, with the surface hardness varying from 8 to 12 GPa. The mathematical models in the form of quadratic polynomials, describing the dependence of the nitrided case depth and surface hardness on the temperature and duration of thermochemical treatment were obtained. The graph-analytical description of variations in the nitrided case depth and surface hardness depending on variations in temperature and duration of treatment, which allows determining the specific conditions of ion nitriding 38Cr2MoAl steel is constructed.